Fabrication, electrical and optical properties of silver, indium tin oxide (ITO), and indium zinc oxide (IZO) nanostructure arrays (Phys. Status Solidi A 5/2013). Issue 5 (17th May 2013) - Khosroabadi, Akram A.; Gangopadhyay, Palash; Duong, Binh; Thomas, Jayan; Sigdel, Ajaya K.; Berry, Joseph J.; Gennett, Thomas; Peyghambarian, N.; Norwood, Robert A.
Abstract Nanostructured metal and transparent conducting oxide electrodes with controllable feature sizes are of major interest to various opto‐electronic devices as they provide a larger interface for the energy transduction processes and nanoscale electronic confi nement resulting in tunable and often exotic optical and electrical properties. Khosroabadi et al. (pp. 831–838) have developed a versatile and powerful new method that enables the lithographic fabrication of nano‐architectured ordered one‐dimensional metal and metal‐oxide electrodes. Optical band gap, electronic carrier concentrations and resistivity of these highly transparent electrodes can be tuned by simply changing the dimensions of the unit nanostructures. A series of samples of silver, pillar‐shaped indium tin oxide and mitre‐shaped indium zinc oxide one‐dimensional nanoelectrodes were fabricated with controlled shapes and surface area enhancement factors up to ∼11 times. These samples were characterized by a number of complementary methods: optical absorption, transmission and refl ection spectroscopy, electrical resistivity measurements, high resolution SEM, energy‐dispersive X‐ray spectroscopy and X‐ray diffraction were used to characterize both in‐depth and lateral structure features, carrier concentrations and band gap values. Detailed fabrication methodology, electrical and optical properties of indium tin oxide, indium zinc oxide and silver electrodes are discussed.